Pengaruh Pengembangan Pegawai dan Insentif serta Lingkungan Kerja Terhadap Kinerja Pegawai UPTD Puskesmas Sungai Merdeka Samboja - Nurazizah Nurazizah; Dirga Lestari AS (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study was conducted by Nurazizah entitled “The Influence of Employee Development, Incentives, and Work Environment on Employee Performance at UPTD Puskesmas Sungai Merdeka Samboja” under the supervision of Dr. Dirga Lestari AS, S.E., M.M. This study aims to analyze the influence of employee development, incentives, and work environment on employee performance at UPTD Puskesmas Sungai Merdeka Samboja. The research method uses a quantitative approach with Partial Least Square (PLS-SEM) analysis technique. The sample in this study consisted of 58 respondents who are employees of UPTD Puskesmas Sungai Merdeka Samboja, with data collection conducted through questionnaires using a Likert scale.The results show that employee development has a positive but not significant effect on employee performance. Meanwhile, incentives and work environment have a positive and significant effect on employee performance. These findings indicate that employee performance is more influenced by appropriate incentive systems and a conducive work environment compared to employee development. Therefore, improving employee performance can be achieved through optimizing incentive systems and enhancing the work environment, along with increasing the effectiveness of employee development programs.